Moth Diversity at Gunung Halimun-Salak National Park, West Java - HARI SUTRISNO (HAYATI Journal of Biosciences, 2008)
A study on moth fauna with focus on macro-moths was conducted at Gunung Halimun-Salak National Park from January to December 2007. The aims of the study were to acquire information of macro-moth diversity and to access the composition of the species at this area. Another objective of the research was to explore undescribed species of moths that inhabit this park. The result showed that a year collecting time with four sampling sites recorded only about 86% of estimated value in this park (846 of 983 species). Index diversity based on Fisheries ? is high. In addition, the number of families recorded from this park is also high, 29 families, or about half of the moth families that occur in Indo-Malayan region. Citiis site was the highest among other sites in term of the diversity index, while Gunung Botol is the lowest. These two sites have a few species in common. In general, Geometridae, Noctuidae, and Pyralidae dominate across all sites. The other significant finding of the research is that Dudgeonidae that has never been recorded from Indonesia was found at Citiis site. Key words: diversity, macro-moths, similarity